2012
DOI: 10.1007/s10228-012-0275-1
|View full text |Cite
|
Sign up to set email alerts
|

Size assortment in mixed-species groups of juvenile-phase striped parrotfish (Scarus iserti) in The Bahamas

Abstract: Striped parrotfish (Scarus iserti) often form heterospecific groups with other reef fishes. In this study, we examined the species and body size composition of these groups on reefs in The Bahamas. Groups averaged approximately 4 S. iserti and 2 associated species, with surgeonfish (Acanthurus chirurgus and A. bahianus), slippery dick (Halichoeres bivittatus), and bluehead wrasse (Thalassoma bifasciatum) as the most common associates. Fewer groups than expected had only 1 associate; groups with 3 or more assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…These two species are known to coexist; H. bivittatus is a common associate in mixed‐species shoals with Scarus spp. (Quinn et al, 2012). Moreover, Scarus spp.…”
Section: Discussionmentioning
confidence: 99%
“…These two species are known to coexist; H. bivittatus is a common associate in mixed‐species shoals with Scarus spp. (Quinn et al, 2012). Moreover, Scarus spp.…”
Section: Discussionmentioning
confidence: 99%
“…However, mixed-species shoals are also frequently found among a wide range of animal taxa and provide advantages in terms of enhanced foraging efficiency and predator avoidance ( Goodale et al, 2010 ; Rodgers, Downing & Morrell, 2015 ; Kleinhappel et al, 2016 ). Although it has long been suggested that the presence of multiple species might change individuals’ behavior and position within the shoal ( Allan, 1986 ), the shoaling behaviors of mixed-species groups have received little attention ( Morse, 1977 ; Ward, Axford & Krause, 2002 ; Quinn et al, 2012 ). Thus, little is known about individual-level interactions within heterospecific groups and the mechanisms mediating their structure ( Kleinhappel et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%